Is This the Gate?: J. M. Coetzee’s Elizabeth Costello and Its Operatic Adaptation - Xingyu Lin (Humanities)
Premiered at the 2024 Adelaide Festival, Is This the Gate? is an opera excerpt composed by Nicholas Lens and set to a libretto written by J. M. Coetzee. It is adapted from the last section of Coetzee’s novel Elizabeth Costello (2003), revolving around the eponymous character’s trial before the gate in the afterworld. This article explores the literary, musical and dramaturgical elements of Is This the Gate? and contends that the adaptation, despite its brevity and incompleteness, indexes and reworks some of the most important intertexts, localities and motifs that connect Coetzee’s early and late works. Allusions to Kafka and Dante frame the scenario for Costello in limbo—a state mirroring a writer’s late-in-life predicament—while references to Australia’s weather and fauna reflect Coetzee’s relationship to his South African roots and adopted home. Further, Costello’s conviction that she is “a secretary of the invisible” holds clues to Coetzee’s deployment of voices and fictional personae since his debut, Dusklands (1974). The last few acts of the opera excerpt evoke themes of desire and mortality that chime with Coetzee’s other Costello narratives, including his latest collection, The Pole and Other Stories (2023). The adaptation ends with Costello’s declaration of her subjectivity, which suggests a writer’s yearning and resolution to go beyond the threshold of life and death.